1992
DOI: 10.1161/01.str.23.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Urgent therapy for stroke. Part I. Pilot study of tissue plasminogen activator administered within 90 minutes.

Abstract: Thrombolytic agents hold theoretical promise as therapy for cerebral infarction. This study was designed to evaluate the safety of tissue plasminogen activator, to accomplish urgent patient treatment, and to estimate potential efficacy of tissue plasminogen activator. Following neurological evaluation and computed tomography of the brain, patients with acute ischemic stroke were evaluated and treated with intravenous tissue plasminogen activator under an open-label, dose-escalation design within 90 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
229
0
7

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(240 citation statements)
references
References 39 publications
4
229
0
7
Order By: Relevance
“…Safety analysis demonstrated that SICH seldom occurred in doses of ≤0.85 mg/kg. 3,4 The NINDS trial, ECASS III trial, and the metaanalysis of them had provided strong evidence for the overall net benefit of standard-dose IV-tPA (0.9 mg/kg, max 90 mg/kg) in AIS within 4.5 hours after symptom onset. 1,2,13 In ECASS, a high dose (1.1 mg/kg) of tPA was tested for AIS within 6 hours from the onset of symptoms, but the occurrence of large parenchymal hemorrhages in the tPA-treated group was significantly more frequent than placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety analysis demonstrated that SICH seldom occurred in doses of ≤0.85 mg/kg. 3,4 The NINDS trial, ECASS III trial, and the metaanalysis of them had provided strong evidence for the overall net benefit of standard-dose IV-tPA (0.9 mg/kg, max 90 mg/kg) in AIS within 4.5 hours after symptom onset. 1,2,13 In ECASS, a high dose (1.1 mg/kg) of tPA was tested for AIS within 6 hours from the onset of symptoms, but the occurrence of large parenchymal hemorrhages in the tPA-treated group was significantly more frequent than placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…SICH was defined as (1) per SITS-MOST, 11 a type 2 intracranial hemorrhage (blood clot >30% of the infarct area, with substantial space occupation) on the 24 to 36 hours follow-up imaging scan after the treatment, combined with a neurological deterioration of >4 points on the NIHSS from the baseline or the lowest NIHSS score between the baseline and 24 hours after thrombolysis or death; (2) per original NINDS study, 1 a hemorrhage that was not seen on a previous cerebral tomographic scan and there had subsequently been either a suspicion of hemorrhage or any decline in neurological status; (3) per European Cooperative Acute Stroke Study (ECASS) II study, 12 any intracranial bleeding, with>4 points worsening on NIHSS score.…”
Section: Outcome Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ECASS 1, a dose ranging study did not show any evidence of a dose response in regard to efficacy 29 ; therefore, a dose similar to acute myocardial infarction (MI) doses was used. In the NINDS trial, dose-ranging studies 16,17 found a dose effect in regard to safety, that higher dose produced more ICHs. This is consistent with thrombolysis trials for acute myocardial infarction in which overdosing, especially in those with low body mass, is a well-established risk factor for ICH.…”
Section: More Might Not Be Bettermentioning
confidence: 99%
“…Local and superselective intra-arterial approaches with relatively low complication rates and high recanalization rates appear promising. [3][4][5][6][7][8][9] The initial studies of IV thrombolysis [10][11][12][13][14][15][16][17] for acute stroke accumulated sufficient data to justify further largescale randomized, double-blinded, placebo-controlled studies. During the 1990s, seven large randomized trials of IV thrombolysis have been reported.…”
mentioning
confidence: 99%